ANALISIS KEBIJAKAN PEMERINTAH DALAM PENGEMBANGAN KERETA CEPAT DI INDONESIA DAN DAMPAKNYA TERHADAP MANAJEMEN PROYEK - Salim, Indra Putra; Simanjuntak, Manlian Ronald A.; Sulistio, Hendrik (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2023)
Fast Train is a modern form of transportation which also signifies the prestige of a country's transportation. Indonesia is one of the countries that will soon have a fast train that runs from Jakarta to Bandung. The ongoing Fast Train is one of the national strategic projects in the infrastructure sector. The Jakarta Bandung Fast Train project itself is targeted to be completed in 2023. During the course of the construction of the Jakarta Bandung Fast Train project, it faced its own difficulties because the Indonesian government's own policies had not properly supported the development of fast trains. This research is based on a review of international experience with high-speed rail projects to develop a recommended high-speed rail policy framework for Indonesia. An international review looked at the development policies of Japan, Taiwan, China and the United Kingdom. The research method that will be used in this study is descriptive qualitative analysis with in-depth literature studies from several journals and regulations related to fast trains. The results of this study indicate that there are several rules or regulations that can be adopted by the Government of Indonesia in the development of fast trains. The steps that need to be taken by the Indonesian government so that the development of fast trains can be sustainable such as appointing or establishing the main agency/institution, special funding sources, and developing regulations and specifications for the design and construction of fast trains to assist in facilitating project management during construction.